Genomic characterization of tumor mutational burden-high breast carcinomas - Theodore Vougiouklakis; Chad Vanderbilt; Satshil Rana; Abhinita Mohanty; Fresia Pareja; Edi Brogi; Christopher Schwartz; Maria E. Arcila; Marc Ladanyi; Hanna Y. Wen; Dara S. Ross (npj Precision Oncology)
Abstract Tumor mutational burden (TMB) has emerged as a potential surrogate for neoantigen load and an indicator of immune checkpoint (IC)-blockade response; however, its precise significance in breast cancer (BC) is not fully understood. Here, we comprehensively characterized the genomic repertoire of BCs with a TMB ≥ 10 mut/Mb (TMB-high [n = 527]) to identify putative predictors of importance. The predominant mutational signature was apolipoprotein B mRNA-editing enzyme catalytic polypeptide (APOBEC) in 64.7% of tumors. TMB-high BCs were enriched in KMT2C, ARID1A, PTEN, NF1, and RB1 alterations, which are associated with APOBEC mutagenesis. Further identified were loss-of-function ARID1A and PTEN alterations, which are linked to immune cell exclusion. ESR1 p.E380Q prevailed among all ESR1 hotspot mutations, supporting APOBEC-mediated effects. Finally, mutations in DNA damage response and repair genes were seen at a higher frequency than in non-TMB-high BCs. These findings provide justification for exploring combined pharmacologic inhibition to improve IC-based efficacy.